CHALLENGES OF CONSERVATION AREA MANAGEMENT IN THE ERA OF REGIONAL AUTONOMY - Rollys Suriani (University of Sumatera Utara, 2017)
This paper is a comprehensive assessment of the conservation area management issues conducted by the government at the local level, it is believed will be faced with the challenge, along with the increasingly implementation of regional autonomy widespread. Various policies issued by local governments wasa consequence of implementation of regional autonomy, not separated with issue of conservation region. Conservation management will be successful if the leaders, associated institution collaborative concern in taking policies to promote conservation areas which require substantial fund management, one factor must change was the pattern of the old paradigm to a whole new paradigm for the interests of conservation areas in the future, both for development purposes and communities interest surrounding conservation areas, with the era of regional autonomy it must also be able to walk together with the vision and mission for the interests of the whole society in general, and not just pursuit of local revenue.